Investigating the Effect of Vitamin A on Orthodontic Tooth Movement: An Experimental Study - Shi, Pengxiang; Zhao, Jing; Wang, Feng (Combinatorial Chemistry & High Throughput Screening, 2025)
BackgroundVitamin A is essential not only for bone metabolism and development but also for the normal functioning of many physiological processes in the body. Despite vitamin A's important involvement in bone metabolism, its effect on orthodontic tooth movement is not entirely known.AimPrevious studies on animals have suggested that vitamin A may influence alveolar bone remodelling and tooth movement, but the effect of various doses of vitamin A on these processes remains poorly understood. This experiment was designed to examine the effect of vitamin A on the orthodontic tooth movement of male rats.MethodsEighty male rats weighing 200-250 grams were divided into eight equal parallel groups. An initial orthodontic force was applied to all groups with a specific appliance, and six different doses of vitamin A were administered (250-2500 IU/Kg intraperitoneally). Two control groups were also considered. Orthodontic tooth movement was measured at the beginning and end of the study period (day 14), and serum alkaline phosphatase (ALP) level was evaluated. The maxillary sections were also evaluated by histological examination.ResultsAlthough there was a dose-dependent increase in tooth movement observed with vitamin A administration, the differences were not statistically significant. There was no significant difference in the number of osteoclasts or the presence of lacunae on the root surface between the study groups. Root resorption was observed in different areas of the root and was not related to different doses of vitamin A. The serum ALP level did not show any significant difference between the groups treated with different doses of vitamin A.ConclusionDespite the known effects of vitamin A on bone metabolism, the results of this study suggest that vitamin A did not increase alveolar bone remodeling and orthodontic tooth movement in male rats.
Keywords: vitamin A